Reproductive planning and pregnancy of HIV serodiscordant couples: a phenomenological study - Tassiane Ferreira Langendorf; Jacqueline Silveira de Quadros; Cristiane Cardoso de Paula; Stela Maris de Mello Padoin; Ivis Emília de Oliveira Souza (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To understand the experience of reproductive planning and pregnancy for HIV serodiscordant couples. Method: Qualitative study, with phenomenological approach, theoretical-philosophical-methodological framework of Martin Heidegger. The field stage took place in a reference service in the care for people living with HIV, in southern Brazil. From an intentional sample, a phenomenological interview was conducted with 11 couples between August 2013 and April 2014. The analysis was hermeneutic. Results: It was possible to understand, from the meaning units that: couples accept and overcome the serological discordance together; experiencing pregnancy is difficult; there is an effort to have a normal life; the diagnosis is silenced by prejudice and stigma; comes the couple's relief after the child's negative diagnosis. Conclusion: It is necessary to recognize the couple as a unit of care with a view to a non-fragmented care in the field of sexual and reproductive health.